Slippage Mitigation and Acoustic Characterisation (SMAC) : Phase 1: sonar adaptation and development of data processing tools /: Phase 1: sonar adaptation and development of data processing tools. (October 2015) - Daworski, Kaj; Fenwick, Alan; Fernandes, Paul
No abstract available